Icelandic parents’/caregivers’ attitudes towards sexuality education - Hilda Björk Friðriksdóttir 1997- (2021)
Sexuality education can provide children, adolescents and young adults with information that can help them make healthy choices when it comes to their sexual health. The aims of this study were threefold: first, to see what kinds of attitudes Icelandic parents/caregivers have towards sexuality education; second, to gauge whom they think should be their child’s primary sexuality educator; and, third, to see what sexuality-related topics should be taught to their children at what age. There were 205 participants, 124 females (60%) and 81 males (40%), who had children in primary-, elementary- and upper secondary school in Iceland. The participants answered an online survey with questions that were based on previous investigations on the same topic. Chi-square test and Pearson Correlations were used to analyze the results. The results showed that the majority of participants thought that sexuality education was important, and that it should be taught cooperatively by schools and parents/caregivers. A large proportion of the participants thought that sexuality education should be taught by an individual with a proper education in sexuality education. Keywords: sexuality education, parents, children, attitudes. Kynfræðsla getur hjálpað börnum, unglingum og ungu fólki að taka upplýstar og heilbrigðar ákvarðanir þegar kemur að kynheilbrigði þeirra. Tilgangur þessara rannsóknar var þríþættur: í fyrsta lagi, til að sjá viðhorf og skoðanir íslenskra foreldra/forráðamanna gagnvart kynfræðslu; í öðru lagi, til að sjá hver ætti að vera aðilinn sem sér um kynfræðsluna; í þriðja lagi, til að sjá hvaða viðfangsefni eru viðeigandi að kenna og á hvaða aldri. Þátttakendur voru í heild 205, 124 konur (60%) og 81 karlar (40%), sem áttu barn/börn í leik-, grunn- og framhaldsskóla á Íslandi. Þátttakendur svöruðu spurningalista sem var dreifður á netinu. Það var notast við Kí-kvaðrat prófið og Pearson fylgni. Niðurstöður sýndu að meirihluti af þátttakendum fannst kynfræðsla vera mikilvæg og ætti að vera kennd í samstarfi milli skóla ...